LYKKEN PÅ FØRTIDSPENSION - VELFÆRDSSTAT OG AFFEKTIV MOBILITET I JENS BLENDSTRUPS GUD TALER UD - Simonsen, Peter (K&K - Kultur og Klasse, 2013)
HAPPINESS ON EARLY RETIREMENT: THE WELFARE STATE AND AFFECTIVE MOBILITY IN JENS BLENDSTRUP’S GUD TALER UD | The article takes its point of departure in current happiness studies and probes the possibly fruitful interdisciplinary relation between research in social science that suggests close links between the Nordic welfare model and the high levels of selfreported happiness we find in the region, and literary criticism which instinctively seems to hold that unhappiness is most conducive to inspire the literary mind. To demonstrate that things are never as simple as that, the article reads Jens Blendstrup’s novel, Gud taler ud (2004), as an example of both a welfare narrative and of what it coins ”an affective mobility story”: a story about a person’s enhanced feeling of happiness in retirement. On the one hand, the novel portrays a person who finds happiness when he is granted early retirement from the welfare state. On the other hand, the novel relates this in such a manner that we are reminded that one man’s happiness may be another’s unhappiness.